2011
DOI: 10.1111/j.1365-3024.2011.01289.x
|View full text |Cite
|
Sign up to set email alerts
|

Cysteine proteinase type I, encapsulated in solid lipid nanoparticles induces substantial protection against Leishmania major infection in C57BL/6 mice

Abstract: Appropriate adjuvant, proper antigen(s) and a suitable formulation are required to develop stable, safe and immunogenic vaccines. Leishmanial cysteine proteinase type I (CPB) is a promising vaccine candidate; nevertheless, it requires a delivery system to induce a potent immune response. Herein, solid lipid nanoparticles (SLN) have been applied for CPB [with and without C-terminal extension (CTE)] formulation to utilize as a vaccine against Leishmania major infection in C57BL/6 mice. Therefore, SLN-CPB and SLN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(13 citation statements)
references
References 30 publications
0
11
0
2
Order By: Relevance
“…They are themselves immunogenic, since L. (L.) mexicana cysteine proteases are T cell immunogen, resulting in the development of potentially protective Thl cell lines. This finding suggests that the cysteine proteases could also be a vaccine candidate and that homologous enzymes in other parasites species may also be so (Khoshgoo et al, 2008;Saffari and Mohabatkar, 2009;Fedelli et al, 2010, Doroud et al, 2011). …”
Section: Cysteine Proteasesmentioning
confidence: 97%
“…They are themselves immunogenic, since L. (L.) mexicana cysteine proteases are T cell immunogen, resulting in the development of potentially protective Thl cell lines. This finding suggests that the cysteine proteases could also be a vaccine candidate and that homologous enzymes in other parasites species may also be so (Khoshgoo et al, 2008;Saffari and Mohabatkar, 2009;Fedelli et al, 2010, Doroud et al, 2011). …”
Section: Cysteine Proteasesmentioning
confidence: 97%
“…96 Another application is vaccine delivery. For example, antigen-loaded solid lipid nanoparticles were efficient in eliciting T H 1 type immune responses and cytokines in mice upon intraperitoneal administration 97 …”
Section: Cytokines As Biomarkers Of Immunomodulatory Properties Ofmentioning
confidence: 99%
“…Studies have shown that encapsulation of antigens in liposomes, nanoparticles, or inclusion of adjuvants greatly enhances their immunogenicity and protective ability, [33][34][35] thus underscoring the need for continued studies in improving vaccine delivery. The development of a vaccine will benefit an estimated 350 million people who are at risk of developing the disease worldwide.…”
Section: Opinion: Benefits Of Continued Researchmentioning
confidence: 99%